Rural landscape and settlement in the Dinas Powys environs: high-resolution analysis of a Roman and medieval pollen sequence at Nant yr Argae in the eastern Vale of Glamorgan - Davies, Tudur; Seaman, Andy; Rippon, Stephen (Medieval Settlement Research, 2025)
This article presents the analysis of a well-preserved Roman and medieval pollen core from the Vale of Glamorgan – the first such analysis from a non-coastal lowland context in south Wales. The sampling site’s environs include the important early medieval promontory fort known as Dinas Powys. Between the mid-third and mid-seventh centuries AD, the pollen record shows considerable fluctuations both before and after the end of Roman administration. The strong pastoral signature seen in the pollen record for the sixth and seventh centuries corresponds with the floruit of Dinas Powys, supporting the view that its wealth was grounded in a local agricultural base. From the eighth and ninth centuries onwards, the overall picture is one of broad continuity. It appears that changes in landownership and tenure were associated with a general continuity of agricultural practice.